FACTORS AFFECTING EMPLOYEE PREMIUMS FOR PALM PALM HARVEST IN KRUENG LUAS GARDEN PT. AGRO SINERGI NUSANTARA - Humayroh; Devi Agustia (RADJA PUBLIKA, 2024)
The data collection technique used in this research uses secondary data. Secondary data is data obtained from a second source, through written sources (library study). Secondary data used are company archives, manuals or reading books related to research problems, journals obtained from the internet and previous theses. The analysis used in this research is multiple linear regression analysis. This analysis is used to analyze factors that are thought to influence the oil palm harvest premium (Y).The results of statistical tests on the effect of harvest premium on age, attendance and production influence the level of harvest premium. The results of the f-test α=0.05 show a significant influence on the production variable (X2) on Variable Y (premium). To identify the coefficient of determination value, you can look at the R-square (R2) value. Based on the regression output, the R2 value is 0.466, meaning that the influence of the harvest premium can be explained well through the regression model built in this research of 46.6%.